Hubungan Tipe Pola Asuh Orang Tua dengan Emotional Quotient (EQ) pada Anak Usia Prasekolah (3-5 Tahun) Di TK Islam Al-Fattaah Sumampir Purwokerto Utara - Achmad, Ika Fadilah; Latifah, Lutfatul; Husadayanti, Dewi Natalia (Jurnal Keperawatan Soedirman, 2010)
Emotional Quotient (EQ) of children is influenced with environment factor, especially with family (parents), that is parents involvement which is reflected in parent’s care pattern. Parent’s care pattern type are democratic, permissive, and authoritarian.The aim of this research is to know the correlation of parent’s care pattern type with EQ preschool children (3-5 years old) in Islam Al-Fattaah Kindergarten Sumampir Purwokerto Utara. The method was analytic correlation with cross sectional approach. The population in this research was 105 people include every parent and every student in Islam Al-Fattaah Kindergarten Sumampir Purwokerto Utara. The sample of this research was 51 respondents during the research from November until December 2009, inclusion and exclusion qualified. Data analysis method with Chi Square. The univariate analysis showed 90,2 % parents in middle adult age, 62,7 % are graduated of college, 58,8 % childrens are 5 years old, and 60,8 % are boys. There were 51 % with democratic care pattern type, 19,6 % with permissive care pattern type, and 29,4 % parents with authoritarian care pattern type. The analysis in children EQ showed 52,9 % high, 29,4 % moderate, and 17,6 % have low EQ. The bivariat analysis of correlation between the parent ’s care pattern type with EQ in preschool children with p < 0,05 show that there is significant correlation the parent’s care pattern type with EQ in preschool children with p= 0,000. Correlation between democratic and authoritarian care pattern type with EQ in preschool children with p < 0,05 shows that there is significant correlation between democratic and authoritarian care pattern type with EQ in preschool children with p = 0,000. Permissive care pattern type shows that there is not significant correlation between permissive care pattern type with EQ in preschool children (p > 0,05, p= 0,090).There is significant correlation between the parent’s care pattern type with EQ preschool children (3-5 years old) in Islam Al-Fattaah Kindergarten Sumampir Purwokerto Utara (p = 0,000).